2021
DOI: 10.1016/j.xfre.2020.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic efficiency of blastocyst culture medium in noninvasive preimplantation genetic testing

Abstract: Objective: To evaluate the diagnostic efficiency of spent blastocyst culture medium (BCM) in noninvasive preimplantation genetic testing (niPGT) by comparing the karyotype concordance with corresponding inner cell mass (ICM) among initial trophectoderm (TE) biopsy, TE re-biopsy, and BCM sampling. Design: Re-analysis aneuploid/mosaic blastocysts donated for research by couples. Setting: Institutional in vitro fertilization center. Patient(s): A total of 12 couples donated their blastocysts, which had previously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 37 publications
0
16
1
Order By: Relevance
“…The number of samples analyzed in all cases was low and the results were heterogeneous: the informativity rate of SBM ranged from 87.5% to 100% whereas the ploidy concordance rates between both types of samples (SBM+BF and TE or WB) were variable, ranging from 76.3% to 100% and from 70.4% to 100%, respectively. Though minimally invasive, this approach did not provide an advantage: no benefit was observed for collapsing the blastocyst to retrieve BF, as the use of BF in combination with SBM did not provide better results than the analysis of the medium itself (Kuznyetsov et al, 2018;Li et al, 2018;Jiao et al, 2019;Zhang et al, 2019b;Kuznyetsov et al, 2020;Chen et al, 2020;Li et al, 2021;Sialakouma et al, 2021) (Table 3).…”
Section: Embryonic Cfdna Analysis For Nipgt-a: Concordance Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of samples analyzed in all cases was low and the results were heterogeneous: the informativity rate of SBM ranged from 87.5% to 100% whereas the ploidy concordance rates between both types of samples (SBM+BF and TE or WB) were variable, ranging from 76.3% to 100% and from 70.4% to 100%, respectively. Though minimally invasive, this approach did not provide an advantage: no benefit was observed for collapsing the blastocyst to retrieve BF, as the use of BF in combination with SBM did not provide better results than the analysis of the medium itself (Kuznyetsov et al, 2018;Li et al, 2018;Jiao et al, 2019;Zhang et al, 2019b;Kuznyetsov et al, 2020;Chen et al, 2020;Li et al, 2021;Sialakouma et al, 2021) (Table 3).…”
Section: Embryonic Cfdna Analysis For Nipgt-a: Concordance Studiesmentioning
confidence: 99%
“…The benefit of such procedure has not been confirmed (Ho et al, 2018). Other manipulations that were performed include vitrification (Xu et al, 2016;Huang et al, 2019;Jiao et al, 2019;Zhang et al, 2019b;Chen et al, 2020;Yin et al, 2021;Shitara et al, 2021;Li et al, 2021), collapsing of the embryo and/or biopsy before media collection (Feichtinger et al, 2017;Kuznyetsov et al, 2018;Huang et al, 2019;Jiao et al, 2019;Zhang et al, 2019b;Chen et al, 2020;Li et al, 2021;Sialakouma et al, 2021). Moreover, there are publications where a completely non-invasive protocol is performed achieving ploidy concordance rates with TE biopsy as high as 84% (Rubio et al, 2019;.…”
Section: ) Is Assisted Hatching (Ah) or Previous Vitrification Needed?mentioning
confidence: 99%
“…When data from 4 such available studies assessing cfDNA in a spent culture medium with or without blastocyst fluid (BF) were combined (7, 29, 36, 37; Supplemental Table 1 [available online]), the false-positive rate (FPR) was significantly improved for niPGT-A versus that for iPGT-A (P ¼ .042) (Table 1). When only 3 studies in which the medium was collected after blastocyst culture (day 5 or 6 or day 6 or 7) (29,36,37) were analyzed, the performance of niPGT-A was superior to that of iPGT-A in terms of FPR (P ¼ .008), positive predictive value (P ¼ .034), and concordance for both embryo ploidy (P ¼ .039) and chromosome copy number variation (P ¼ .024) (Table 2). These data indicated that niPGT-A was less prone to errors associated with embryo mosaicism and was more reliable than iPGT-A, a conclusion consistent with the 3-proven efficacy to improve clinical pregnancy and live birth rates (43), one is, indeed, forced to ask what, under current circumstances, the potential benefits to infertile couples are from any form of PGT-A, whether by teBx or cfBx.…”
Section: What Additional Evidence Is Needed To Support the Con?mentioning
confidence: 99%
“…According to some research groups, niPGT-A has comparable diagnostic efficiency to TE-biopsy PGT-A [ 22 , 24 , 27 ]. Moreover, niPGT-A using SCM may be more reliable than initial TE biopsy for predicting karyotypes of ICM in mosaic embryos [ 22 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%